Using dopping and adsorption to introduce energy band gap into graphene ; a DFT study - Issa Z.Hassan,Enas M.Ali (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is essential introducing and tuning an energy band gap to graphene for the promising electronic and optoelectronic application of this 2D carbon nanostructure.In the natural state, graphene cannot be used in electronic nanoscale applications because graphene is a semiconductor with a nearly zero band gap energy, which behaves like a semi-metal, as it is necessary to open the band gap energy values of graphene for use in various nanoscale applications as a semiconductor material with different band gap.Investigate the co-doping method .Materials Studio simulation tool ,based on Density Functional TheoryDFT and Local Density Approximation (LDA) to study doping and adsorption large unit cell (4x4x1) for graphene to opening different values of band gap energy . We have been observed different band gap energy between (0.084 eV – 0.77 eV), These values of band gap energy converting graphene from a semiconductor with a gap almost zero to semiconductor with different values of band gap energy.